Estimation of 238U, 232Th and 40K concentrations in rock and soil samples around South Purulia Shear Zone, India. (1st January 2013) - Mittal, Saurabh; Guin, R.; Sharma, S.P.; Sengupta, D.
The first few measurements for low level gamma ray spectrometry for the delineation of U and Th along South Purulia Shear Zone (SPSZ) are reported. Estimation of 238 U, 232 Th and 40 K concentrations in widely dispersed rock and soil samples around SPSZ has been undertaken using HPGe detector having relative efficiency of 50%. The maximum concentration among all the samples studied is observed in the sample close to the Beldih region, SPSZ. An attempt has been made to study the variation in the concentration of these rock and soil samples with respect to location from the shear zone. Central part of the shear zone is found to contain higher concentration of radionuclides than the samples from the periphery. This proves that intensity of shearing controls the activity of radionuclides in a sample, apart from alteration, metamorphism, weathering, etc. A comparison of radionuclide activities of soil samples in study area with other studies worldwide is reported.